Analysis of Capital Structure of Small scale and Medium Manufacturing Enterprises in England - Rao, Prarthana Nagaraj (2010)
This research examines a panel data set of 122 small and medium manufacturing firms between the years 2005 and 2009 to explore their determinants of capital structure, whose influence is tested before and after the financial crisis in 2008. Using the random effect model in STATA, the effect of the determinants, which include profitability, growth, asset structure, firm size, age and the volatility of the firms on the long term debt and the short term debt are investigated, by drawing out a comparison of the trends between the pre-crisis and the post-crisis phase. The study shows that the profitability and asset structure are significantly associated with the long term and short term debt structure of the firms. The other factors like growth, firm size, age and volatility do not contribute significantly to the capital structuring of these manufacturing small scale and medium firms situated in England. The firms seem to have been considerably impacted by the financial crisis because of the overall reduction in the average values of all the proxies of the determinants.